Dziecko z rodziny alkoholików w środowisku szkolnym - Schmidt , Anna (Studia Edukacyjne, 2020)
The article concerns the child from an alcoholic family in a pre-school environment. The author presents a theoretical introduction on definitions important for understanding the subject, then addresses the subject of social pathology as a factor disturbing the durability of the family system. The topic of social roles in the alcoholic family and their impact on the child’s socialization process continue to arouse interest. Another issue raised in the article is the topic of co-dependence, starting from the general definition and understanding of the concept and ending with the impact of this phenomenon on the child’s functioning. The issue analyzed and reflected is as follows: a child from an alcoholic family as a student – in particular in relationships with teachers and peers. The author reflected moreover on the possible difficulties a child in a pathological family may encounter in the school environment, as well as on suggested practical solutions and a support network that may help the individual and its immediate environment to fight against difficulties and to motivate change. The article has an introduction and ending, which aptly sums up the issues dealt with.